Editorial Note - Chakravarty, Rupak (International journal of information studies and libraries, 2017)
Libraries as Viable Systems: According to the Viable System Theory (VST), which emphasize on the development/evolution of dynamic systems, Viable Systems are considered to be living systems in the sense that they are complex and adaptive, can learn, and are capable of maintaining an autonomous existence, at least within the confines of their constraints. The Viable System Model (VSM) is a model of the organizational structure of any autonomous system capable of producing itself. The model was developed by operations research theorist and cybernetician Stafford Beer in his book Brain of the Firm (1972). Organizations following the principles of viable system are capable of maintaining the internal stability and autonomy through adaptation in order to meet the demands of surviving in the changing environment. Libraries can excel if they emulate the attributes of a VSM like dynamic, living, complex and adaptive, learn, capable of maintaining an autonomous existence, recursive. Applying Viable System Theory (VST) to libraries or viewing them as Viable System Model (VSM) would be very interesting. But libraries as VSMs can be argued if we are able to correlate it to emerging phenomena and principles surrounding and effecting libraries. In times when questions are being raised, libraries need to find viable answers and solutions. Libraries losing their charm & sheen on account of diverse factors need to revive, reincarnate and resurrect by imbibing cloud computing/storage, Internet of Things (IoT), Big Data, mobile technologies, subject guides and Embedded Librarianship. Resurgent libraries can play a crucial role in the creation of unprecedented knowledge capital thus contributing in nation building.